ANALISIS PELAYANAN PEMBAYARAN PAJAK BUMI DAN BANGUNAN DI KPP PRATAMA KOTA PADANG - Ingra Sovita Ingra Sovita; Enny Arita Enny Arita (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2018)
Community participation in paying PBB (Land and Building Tax) is still low because services are not optimal in the Primary KPP of Padang. Research objective to analyze UN payment services. Research population 350 people and samples of 85 people taken by accidental sampling by random sampling. Collecting techniques with observation, interviews and questionnaires were analyzed using qualitative descriptive. The results ofUN payment research in the KPP Pratama city of Padang showed: 1) the implementation of UN payments was still simple and quite difficult, 2) the procedures for PBB payment services were good enough, 3) the efficiency of UN services was not good. Obstacles in the implementation of PBB payments from the Primary KPP of Padang city, especially in thefields of administration, operational fields and services. Obstacles in implementing UN payments from taxpayers as follows: 1) low education and knowledge about taxpayers, 2) low awareness of paying the United Nations, 3) overlapping UN payments.